2005
DOI: 10.5194/angeo-23-3699-2005
|View full text |Cite
|
Sign up to set email alerts
|

Wave particle interactions in the high-altitude polar cusp: a Cluster case study

Abstract: Abstract. On 23 March 2002, the four Cluster spacecraft crossed in close configuration (∼100 km separation) the high-altitude (10 R E ) cusp region. During a large part of the crossing, the STAFF and EFW instruments have detected strong electromagnetic wave activity at low frequencies, especially when intense field-aligned proton fluxes were detected by the CIS/HIA instrument. In all likelihood, such fluxes correspond to newly-reconnected field lines. A focus on one of these ion injection periods highlights th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 39 publications
4
58
0
Order By: Relevance
“…The latter possibility has also been discussed by Sundkvist et al (2005), who suggest that the cusp waves belong to the kinetic Alfvén branch below the proton cyclotron frequency and are electromagnetic ion-Bernstein waves above that frequency. This is also confirmed by Grison et al (2005) who used the k-filtering technique, and showed that kinetic Alfvén waves dominate the electromagnetic spectrum up to 1Hz and above 0.8 Hz intense Bernstein waves are observed.…”
Section: Introductionsupporting
confidence: 62%
“…The latter possibility has also been discussed by Sundkvist et al (2005), who suggest that the cusp waves belong to the kinetic Alfvén branch below the proton cyclotron frequency and are electromagnetic ion-Bernstein waves above that frequency. This is also confirmed by Grison et al (2005) who used the k-filtering technique, and showed that kinetic Alfvén waves dominate the electromagnetic spectrum up to 1Hz and above 0.8 Hz intense Bernstein waves are observed.…”
Section: Introductionsupporting
confidence: 62%
“…The intermediate mode is only slightly damped at higher frequencies since the average ratio |g|/w r is about 0.1, with a maximum of less than 0.25 (g is the damping rate and w r is the real part of the frequency), which suggests that this wave mode is likely to be observed in the diffusion region. We note that, under the present condition of a high b and high oblique propagations, the fast magnetosonic mode splits into Bernstein modes [Grison et al, 2005;Howes, 2009].…”
Section: Huang Et Al: Waves In Reconnection Region A12211 A12211mentioning
confidence: 99%
“…strong magnetic and electric waves are generated in the cusp region as noticed in case studies (e.g. Grison et al, 2005) and statistical studies (e.g. Cargill et al, 2005).…”
Section: Single-point Observationsmentioning
confidence: 76%